2007
DOI: 10.1002/cncr.22587
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for activation of KIT, PDGFRα, and PDGFRβ receptors in the Ewing sarcoma family of tumors

Abstract: BACKGROUND. The Ewing sarcoma family of tumors (ESFT) is one of the most common malignant neoplasms of children and adolescents, characterized by nonrandom translocations involving the Ewing sarcoma (EWS) gene. Over the years the adoption of intensive multimodality treatment approaches has led to a gradual improvement in the survival of patients with ESFT. The prognosis is still unsatisfactory for high‐risk patients, however, and novel therapeutic approaches are desirable. The aim of the study was to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 22 publications
0
25
0
3
Order By: Relevance
“…Expression of VEGFA, the ligand of KDR, has been shown to associate with poor prognosis in sarcomas, including osteosarcoma and Ewing sarcoma [ (Lee et al, 1999;Kaya et al, 2000;Fuchs et al, 2004), reviewed in (DuBois and Demetri, 2007)], and in one study on nonmetastatic osteosarcoma, the expression of KDR was found in 67% of the patients (Lee et al, 1999). Expression of the normal KIT receptor has been reported in many neoplasms, including osteosarcoma and Ewing sarcoma (Sulzbacher et al, 2003;Tamborini et al, 2004;Burger et al, 2005;Entz-Werle et al, 2005;McIntyre et al, 2005;Bozzi et al, 2007).…”
Section: Copy Number Changes In Ups Of Bonementioning
confidence: 96%
See 1 more Smart Citation
“…Expression of VEGFA, the ligand of KDR, has been shown to associate with poor prognosis in sarcomas, including osteosarcoma and Ewing sarcoma [ (Lee et al, 1999;Kaya et al, 2000;Fuchs et al, 2004), reviewed in (DuBois and Demetri, 2007)], and in one study on nonmetastatic osteosarcoma, the expression of KDR was found in 67% of the patients (Lee et al, 1999). Expression of the normal KIT receptor has been reported in many neoplasms, including osteosarcoma and Ewing sarcoma (Sulzbacher et al, 2003;Tamborini et al, 2004;Burger et al, 2005;Entz-Werle et al, 2005;McIntyre et al, 2005;Bozzi et al, 2007).…”
Section: Copy Number Changes In Ups Of Bonementioning
confidence: 96%
“…Frequent gains at the 4q12 region, including high level amplifications, have been reported in osteosarcoma, too Man et al, 2004). Involvement of PDGF receptors and their ligands have been suggested in sarcomas, as in osteosarcoma and Ewing sarcoma [ (Sulzbacher et al, 2003;Bozzi et al, 2007), reviewed in (DuBois and Demetri, 2007)], and the expression of PDGF-AA homodimer has been reported to associate with tumor progression in osteosarcoma (Sulzbacher et al, 2003). Expression of VEGFA, the ligand of KDR, has been shown to associate with poor prognosis in sarcomas, including osteosarcoma and Ewing sarcoma [ (Lee et al, 1999;Kaya et al, 2000;Fuchs et al, 2004), reviewed in (DuBois and Demetri, 2007)], and in one study on nonmetastatic osteosarcoma, the expression of KDR was found in 67% of the patients (Lee et al, 1999).…”
Section: Copy Number Changes In Ups Of Bonementioning
confidence: 99%
“…Although the prevalence of PDGFRA genetic aberrations in pediatric cancer is reported to be only about 2% (19), members of the PDGF pathway are highly expressed in several subtypes of pediatric bone and soft tissue tumors, including rhabdomyosarcoma (20,21), synovial sarcoma (22), osteogenic sarcoma (23), Ewing sarcoma (24), and MRT (25). In addition, PDGFRa expression is linked to adverse outcomes in pediatric patients with rhabdomyosarcoma (26).…”
Section: Introductionmentioning
confidence: 99%
“…PDGFR is expressed in all three types of childhood sarcomas discussed here (33)(34)(35) and c-kit expression has been found in Ewing's sarcoma and osteosarcoma (36)(37)(38). Mutations were only found in the case of c-kit and in a small fraction of Ewing's sarcomas (39).…”
Section: Receptor Tyrosine Kinasesmentioning
confidence: 95%
“…Mutations were only found in the case of c-kit and in a small fraction of Ewing's sarcomas (39). However, both PDGFR and c-kit are activated in these childhood sarcomas (37,40) and PDGF was found to act as mitogen for osteosarcoma cells (41). Furthermore, expression of PDGF-AA was found to be associated with tumor progression in osteosarcoma (42).…”
Section: Receptor Tyrosine Kinasesmentioning
confidence: 99%